Albendazole Solid Dispersions: Influence of Dissolution Medium Composition on In Vitro Drug Release - González Vidal, Noelia Luján (2014)
The rate-limiting step to drug absorption is often dissolution from the dosage form, especially for poorly soluble com-pounds. Two possibilities for improving the dissolution of these drugs are to increase the available surface area and to im-prove their apparent solubilities under physiologically relevant conditions with surfactants as wetting agents. Albendazole (ABZ), one of the most effective broad-spectrum antihelminthic agents, has a very low aqueous solubility, which leads to an erratic availability. Solid dispersions (SD) with different amounts of carriers (P188 and PEG6000) were formulated to improve the ABZ dissolution rate. When the dissolution test is used to infer biopharmaceutical properties of the dosage form, it is es-sential that the method simulates the gastrointestinal conditions. The objective of this study was to examine the applicabil-ity of different dissolution media to the evaluation of ABZ and ABZ-SD dissolution rates. Dissolution profiles were performed by the official method (0.1 N HCl) and Simulated Gastric Fluid modified with a surfactant. Wetting was evaluated through the determination of surface tension and contact angle of the solutions. The dissolution rate of ABZ was clearly affected by the variables assessed in this study. These results have implications in the design of physiologically based dissolution media.